Association of Selenium and Thyroid Cancer: A Comprehensive Systematic Review - Setiawan Nathan, Daniel; Yumilia, Hoo (The International Journal of Medical Science and Health Research, 2024)
Introduction: Selenium's historical journey from discovery to its role in human health underscores its complex relationship with disease, particularly thyroid cancer. While research suggests a potential link between low selenium levels and thyroid cancer risk, conflicting findings challenge our understanding of selenium's impact, warranting further investigation. This systematic review aims to unravel selenium's intricate interplay with thyroid cancer, navigating through its historical significance, physiological role, and recent epidemiological studies to offer insights into this complex relationship. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 18 results. After looking at the titles and summaries, we found 7 papers that fit our criteria. At first, we excluded several articles because they were written in review style, pilot study, and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included experimental study, cross-sectional study, prospective cohort, and case control. Conclusion: This systematic review explores the relationship between selenium and thyroid cancer, highlighting SBP1 as a potential therapeutic target based on experimental evidence. Clinical studies suggest lower serum selenium levels in females with papillary thyroid cancer, indicating a potential protective effect with higher selenium levels. While the development of a tumor-targeted drug delivery system shows promise for thyroid cancer treatment, a large prospective cohort study found no association between selenium intake and thyroid cancer risk, emphasizing the need for further research, particularly biomarker-based studies.